Timeevolving radiative feedbacks in the historical period - Salvi,P; Gregory,JM; Ceppi,P (Journal of Geophysical Research: Atmospheres, 2023)
We investigate the time-dependence of radiative feedback in the historical period (since the late 19th century), by analyzing experiments using coupled atmosphere–ocean climate models with historical greenhouse gas, anthropogenic aerosol, and natural forcings, each separately. We find that radiative feedback depends on forcing agent, primarily through the effect of cloud on shortwave radiation, because the various forcings cause different changes in global-mean tropospheric stability per degree of global-mean temperature change. The large time-variation of historical feedback driven by observed sea surface temperature change alone, with no forcing agents, is also consistent with tropospheric stability change, and differs from the similarly large and significant historical time-variation of feedback that is simulated in response to all forcing agents together. We show that the latter results from the varying relative sizes of individual forcings. We highlight that volcanic forcing is especially important for understanding the time-variation, because it stimulates particularly strong feedbacks that tend to reduce effective climate sensitivity. We relate this to stability changes due to enhanced surface temperature response in the Indo-Pacific warm pool.